The chronopolitics of national populism. Issue 2 (4th March 2022) - Taş, Hakkı
ABSTRACT: Inspired by the populists' salient urge to recalibrate and locate contingent developments within a larger temporal order and establish historical continuity, this paper dwells on the chronopolitics of national populism and calls for a systematic treatment of time in these movements. Focusing on the neglected narrative dimension, such an inquiry will afford an alternative reading from which to engage with and critique the magnitude of populism. This study argues that despite ample variance and claims of uniqueness, national populisms employ a shared temporal template that accounts for a particular national subjectivity through a set of timing and sequencing of events complemented by affective stimuli. It focuses on the case of Turkey. More pronounced since 2013 Gezi Protests, the rising tide of national populism under President Tayyip Erdoğan's rule encapsulates how these populisms conflate the past, present, and future into a single narrative about the people's survival and prosperity.